Cytotoxicity and genotoxicity of thymol verified in murine macrophages (RAW 264.7) after antimicrobial analysis in Candida albicans, Staphylococcus aureus, and Streptococcus mutans - Belato, Kely Karina [UNESP]; de Oliveira, Jonatas Rafael [UNESP]; de Oliveira, Fernanda Saraiva [UNESP]; de Oliveira, Luciane Dias [UNESP]; Camargo, Samira Esteves Afonso [UNESP] (Elsevier, 2018)
Thymol is a phytocompound present in many plants and several biological effects have been reported, such as antimicrobial effect. However, the biocompatibility of this plant product should be checked. Thereby, the action of thymol was evaluated in C. albicans, S. aureus, and S. mutans, as well as in murine macrophages (RAW 264.7). Firstly, the effect of thymol was analyzed in planktonic cultures of microorganisms and the most effective concentration was evaluated in biofilms. Cytotoxicity, quantification of TNF-α and genotoxicity were checked. The results were analyzed by T-Test or ANOVA and Tukey's Test (P ≤ .05). Thymol provided inhibitory and microbicidal effects for planktonic cultures and reduction of biofilms. High concentrations affected the viability of RAW 264.7. Production of TNF-α and frequency of micronuclei were similar to the control group. Thus, thymol showed antimicrobial effect, biocompatibility in some concentrations and absence of genotoxicity.
Keywords: Antimicrobial activity; Cytotoxicity; Genotoxicity; Thymol; TNF-α